1999
DOI: 10.3168/jds.s0022-0302(99)75229-x
|View full text |Cite
|
Sign up to set email alerts
|

Bile Tolerance, Taurocholate Deconjugation, and Binding of Cholesterol by Lactobacillus gasseri Strains

Abstract: Bile tolerance, deconjugation of sodium taurocholate, and the cholesterol-binding ability of 28 strains of Lactobacillus gasseri were examined. There was significant variation among strains in growth in media containing bile and also variation in the ability to bind cholesterol. Cultures grown for 12 h at 37 degrees C bound significantly more cholesterol than did cells from a 48-h incubation. Variation among strains in the ability to deconjugate sodium taurocholate was not significantly different. Maximal deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(97 citation statements)
references
References 22 publications
5
90
1
1
Order By: Relevance
“…Result of serum analysis in this study found that the addition of probiotics tended to reduce TC, LDL, TRIG and increase HDL, but only VLDL was significantly (PO.05) reduced by using probiotics. This result agreed with the findings of some in vitro (Gilliland et al, 1985;Brashears et al, 1998;Usman, 1999), or in vivo studies (De Rodas et al, 1996;Noh et al, 1997).…”
Section: Resultssupporting
confidence: 82%
“…Result of serum analysis in this study found that the addition of probiotics tended to reduce TC, LDL, TRIG and increase HDL, but only VLDL was significantly (PO.05) reduced by using probiotics. This result agreed with the findings of some in vitro (Gilliland et al, 1985;Brashears et al, 1998;Usman, 1999), or in vivo studies (De Rodas et al, 1996;Noh et al, 1997).…”
Section: Resultssupporting
confidence: 82%
“…Considering bile tolerance an important characteristic of probiotic microorganisms, it has been reported that 0.3% oxgall closely appropriates the bile level of the human gastrointestinal tract, and the concentration of 0.3% bile salts has been considered crucial for screening and selection of human probiotics [25,26]. However, survival of lactobacilli at pH value of 3 for 2 h and at a bile concentration of 0.1% has also been considered optimal acid and bile tolerance for strains to be used as probiotics [27]. Liong and Shah [13] stated that resistance at pH 3 has been the standards for acid tolerance of probiotic culture.…”
Section: Discussionmentioning
confidence: 99%
“…Tolerance to acidic condition is the most commonly used method to detect the viability and activity of probiotic bacteria in the small intestine and stomach. According to a previous study (Usman and Hosono, 1999), the survival rate at pH 3.0 is considered as optimal acid tolerance for selected probiotic strains. All strains from this study were able to tolerate pH 3.0 with a survival percentage of more than 70%, and therefore they can be considered as acidtolerant LAB strains.…”
Section: Discussionmentioning
confidence: 99%